2020
DOI: 10.1074/jbc.ra120.014062
|View full text |Cite
|
Sign up to set email alerts
|

CaMKII enhances voltage-gated sodium channel Nav1.6 activity and neuronal excitability

Abstract: Nav1.6 is the primary voltage-gated sodium channel isoform expressed in mature axon initial segments and nodes, making it critical for initiation and propagation of neuronal impulses. Thus, Nav1.6 modulation and dysfunction may have profound effects on input-output properties of neurons in normal and pathological conditions. Phosphorylation is a powerful and reversible mechanism regulating ion channel function. Because Nav1.6 and the multifunctional Ca2+/CaM-dependent protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(60 citation statements)
references
References 112 publications
(146 reference statements)
2
57
0
Order By: Relevance
“…The possibility, though, that Ca 2+ entry via T-type Ca 2+ channels may also rapidly and reversibly phosphorylate Na + channels to enhance the persistent Na + current in ventral mEC layer II stellate neurons cannot be excluded. Certainly Ca 2+ -dependent modification of Na V 1.6 channels, which principally encode for persistent Na + currents in neurons (Hargus et al, 2013; Katz et al, 2018), increased the persistent Na + current in hippocampal CA1 pyramidal neuronal dendrites (Yu et al, 2018) and cerebellar Purkinje neurons (Zybura et al, 2020). Moreover, Ca 2+ - calmodulin dependent kinase, CaMKII, phosphorylates Na V 1.2 channels, that predominantly underlie transient Na + currents, to generate a persistent Na + current in heterologous systems (Thompson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility, though, that Ca 2+ entry via T-type Ca 2+ channels may also rapidly and reversibly phosphorylate Na + channels to enhance the persistent Na + current in ventral mEC layer II stellate neurons cannot be excluded. Certainly Ca 2+ -dependent modification of Na V 1.6 channels, which principally encode for persistent Na + currents in neurons (Hargus et al, 2013; Katz et al, 2018), increased the persistent Na + current in hippocampal CA1 pyramidal neuronal dendrites (Yu et al, 2018) and cerebellar Purkinje neurons (Zybura et al, 2020). Moreover, Ca 2+ - calmodulin dependent kinase, CaMKII, phosphorylates Na V 1.2 channels, that predominantly underlie transient Na + currents, to generate a persistent Na + current in heterologous systems (Thompson et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the aberrant phosphorylation of CaMKII is the cause of neurological symptoms of Angelman syndrome [ 39 ]. However, since CaMKII is expressed most abundantly in neurons, it regulates many aspects of neuronal function, including neurotransmitter synthesis and release, modulation of ion channel activity, cellular transport, cellular morphology, and neurite extension [ 76 , 77 , 78 , 79 ].…”
Section: Camkiimentioning
confidence: 99%
“…Studies showed that this kinase regulates the conductivity of the various types of sodium, potassium, and calcium channels [ 84 ]. Considering the neuronal cells, CaMKII enhances voltage-gated sodium channel Nav1.6 activity and neuronal excitability [ 79 ]. Moreover, by modulating the voltage-gated calcium (CaV)2.1 channels that conduct P/Q type Ca 2+ currents, CaMKII regulates the neurotransmitter release [ 85 ].…”
Section: Camkiimentioning
confidence: 99%
“…Since the first CaMKII inhibitor, KN-62 was invented in experiment (Tokumitsu et al, 1990); more and more drugs targeting CaMKII were discovered. Yet most of drugs are still utilized in animal models, only three specific CaMKII inhibitors, rimacalib (SMP-114), tatCN21 (Zybura et al, 2020), and ranolazine are applied in clinical trials, so there is still a long journey to the development of CaMKII-related medicine and its utilization in myocardial I/R injury. Meanwhile, many commonly used drugs have effect on CaMKII suppression, which is also unfavorable to the passion of targeting CaMKII invention.…”
Section: Calmodulin-dependent Protein Kinase II Inhibitionmentioning
confidence: 99%